Optimización del modelo de atención presencial a usuarios en la agencia pública de empleo en el Sena regional Norte de Santander buscando impactar positivamente en el acceso al empleo en la ciudad. - Daniel López-Montañez; Francisco Raúl Arencibia-Pardo; Belisario Peña-Rodríguez (Mundo Fesc)
With the SENA Public Employment Agency as the study center, which plays a fundamental role in job placement and labor market development in the Norte de Santander region and is crucial for citizens' job placement, the main objective of this research is to evaluate the in-person service model offered by this agency in its regional operations. The objective is to analyze the effectiveness and efficiency of this model, identify areas for improvement, and propose recommendations to optimize service delivery and enhance the user experience in their job search.